2014
DOI: 10.3390/molecules19033793
|View full text |Cite
|
Sign up to set email alerts
|

Antischistosomal Activity of the Terpene Nerolidol

Abstract: Schistosomiasis is a neglected tropical disease that affects hundreds of millions of people worldwide. Since the treatment of this disease currently relies on a single drug, praziquantel, new and safe schistosomicidal agents are urgently required. Nerolidol, a sesquiterpene present in the essential oils of several plants, is found in many foods and was approved by the U.S. Food and Drug Administration. In this study we analysed the in vitro antiparasitic effect of nerolidol on Schistosoma mansoni adult worms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 43 publications
(49 reference statements)
1
36
1
2
Order By: Relevance
“…Generally, if a drug induces tegumental alterations, the onset and precise pattern of these alterations depend on the particular drug and the treatment regimen used (44) . The characteristic features of tegumental damage observed in this study, including destruction of the tegument and erosion and loss of spines, were consistent with those previously described in the literature following in vitro exposure to different antischistosomal agents such as hypericin (45) , allicin (46) , nerolidol (47) , phthalyl thiazole (LpQM-45) (48) , β-lapachone (49) , and DNK (32) . Hence, reductions in worms may be attributed to the tegumental damage observed.…”
Section: Discussionsupporting
confidence: 76%
“…Generally, if a drug induces tegumental alterations, the onset and precise pattern of these alterations depend on the particular drug and the treatment regimen used (44) . The characteristic features of tegumental damage observed in this study, including destruction of the tegument and erosion and loss of spines, were consistent with those previously described in the literature following in vitro exposure to different antischistosomal agents such as hypericin (45) , allicin (46) , nerolidol (47) , phthalyl thiazole (LpQM-45) (48) , β-lapachone (49) , and DNK (32) . Hence, reductions in worms may be attributed to the tegumental damage observed.…”
Section: Discussionsupporting
confidence: 76%
“…The terpenes with antischistosomal activity are: rotundifolone [66], (+)-limonene epoxide [56], and carvacryl acetate, a derivative of carvacrol (monoterpenes) [39]; artemisinin and its derivatives [30,31], nerolidol [59], and budlein-A and its derivatives [38] (sesquiterpenes); phytol [60] (diterpene), betulin [37] and its triphenylphosphonium derivatives [69], balsaminol F, karavilagenin C [36] (triterpenes) (Figure 1). Importantly, among the group of terpenes, in vitro and in vivo antischistosomal properties have been described only for artemisinin and its derivatives, phytol and triphenylphosphonium derivatives, whereas it was reported in vitro schitosomicidal activity for other terpenes (Table 1).…”
Section: Terpenesmentioning
confidence: 99%
“…Different responses in antischistosomal drugs susceptibility between male and female S. mansoni worms have been described by Silva et al [24], were males are more sensible to the nerolidol terpene. On the other hand, Mitsui et al [29], show that S. mansoni females are more sensible to artesunate sesquiterpene.…”
Section: Discussionmentioning
confidence: 91%
“…Other authors observed similar tegumental alterations after evaluating different sesquiterpenes in vitro. e.g Dihydroartemisinin 4a,5-dihydrobudlein A, Nerolidol [22][23][24].…”
Section: Discussionmentioning
confidence: 99%